2018
DOI: 10.1111/echo.14009
|View full text |Cite
|
Sign up to set email alerts
|

Isolated premature restriction or closure of foramen ovale in fetuses: Echocardiographic characteristics and outcome

Abstract: Premature rFO/cFO are rare in fetuses with otherwise structurally normal hearts. The fetal echocardiographic characteristics include right atrial and ventricular dilated, tricuspid regurgitation, and pericardial effusion. Most fetuses had a good outcome, although there was an association between rFO, especially cFO, with neonatal morality and complications (prematurity, maternal preeclampsia and placental abruption, hydrops fetalis, and necrotizing enterocolitis with perforation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 21 publications
0
32
1
Order By: Relevance
“…Several authors have reported RV to LV growth discrepancy and mild to moderate hypoplasia of the mitral and aortic valves as well as the aortic arch 7,8 , others described LV dilatation and fibro-elastosis 9 . While RV dilation, tricuspid regurgitation, pericardial effusion, pleural effusion, in-utero heart failure and hydrops fetalis as well as early and late pulmonary hypertension have also been reported [10][11][12][13][14] , there is substantial evidence that early (primary) closure of the FO results in hypoplasia of left heart structures and that normal fetal left heart development is dependent on a normal volume of flow though the FO 9,15 .…”
mentioning
confidence: 99%
“…Several authors have reported RV to LV growth discrepancy and mild to moderate hypoplasia of the mitral and aortic valves as well as the aortic arch 7,8 , others described LV dilatation and fibro-elastosis 9 . While RV dilation, tricuspid regurgitation, pericardial effusion, pleural effusion, in-utero heart failure and hydrops fetalis as well as early and late pulmonary hypertension have also been reported [10][11][12][13][14] , there is substantial evidence that early (primary) closure of the FO results in hypoplasia of left heart structures and that normal fetal left heart development is dependent on a normal volume of flow though the FO 9,15 .…”
mentioning
confidence: 99%
“…Gu et al reported a series of 60 foetuses with restrictive foramen ovale and 5 with closed foramen ovale. 1 In one of the foetuses with closed foramen ovale, authors observed decreased systolic function of both ventricles and hydrops. The patient was delivered very preterm and died after birth.…”
Section: Discussionmentioning
confidence: 97%
“…2 However, due to a small number of reported patients, clinical and echocardiographic findings are less clearly defined in patients with closed foramen ovale. 1,2 Furthermore, the left heart function was not clearly evaluated in these patients. Therefore, we report a patient who was diagnosed immediately after birth with closed foramen ovale, severe persistent pulmonary hypertension of the newborn, and profound left heart failure.…”
mentioning
confidence: 97%
See 2 more Smart Citations